COGNITIVE MAPPING IN THE WRITING CLASSROOM: RETHINKING HOW STUDENTS ORGANIZE AND EXPRESS IDEAS - Fitrianti Putri; Umar Abdullah; Fitri Alya Okta Sukma (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2025)
Many senior high school students struggle with initiating and organizing their ideas, applying grammar accurately, and maintaining cohesion in their writing. Mind mapping is a visual technique that enables students to brainstorm ideas, establish connections, and structure content in a non-linear format. This study investigated the effect of using mind mapping on the writing ability of tenth-grade students at SMA Negeri 14 Palembang. The study used a quantitative method comparing a group taught using mind mapping (the experimental group, 34 students) and a group taught in the usual way (the control group, with 34 students) before and after the treatment. The students’ writing ability was measured with a writing test before and after the treatment. Because the test results were not normally distributed, nonparametric statistical tests were used to analyze the data. The Wilcoxon Signed-Rank Test revealed that the writing ability of the experimental group improved significantly after using mind mapping. Furthermore, the Mann-Whitney U test showed a significant difference in writing test scores between the experimental and control groups after treatment, with the experimental group scoring better. The findings of this research indicated that using mind mapping greatly helped to improve the tenth-grade students’ writing ability in recount text. This study suggests that teachers could use mind mapping as a way to enhance students’ writing skills.